A COMPARISON OF RTK-GPS VERTICAL COMPONENT WITH PRECISE DIGITAL LEVEL FOR ESTIMATING VOLUMES - ZAIA, YOUSIF YOUKHANNA; ADAM, SARHAT MUSTAFA; GILYANA, SAMI MAMLOOK (Journal of Duhok University, 2017)
In this research, RTK GPS (Real time Kinematic GPS) was used to compare with precise Digital Level for estimating earthwork volumes. Any volume calculation process has to pass through two stages. Firstly, data collection using surveying instrument, for instance, level instrument, total station, Global Positioning System (GPS), or laser scanning. In the second stage, carrying out measurement of figuring volumes using either manual or computerized method. In this paper, the field test was conducted to gather data for estimating earthworks using two technologies; Digital Level (DNA 03) and RTK GPS. Two sites have been chosen; open to the sky and partially obstructed to satellites in order to evaluate RTK GPS technique. The main aim is to compare the RTK manufacturer claimed accuracy (height component only) with trusted data. The comparison has been carried out using two different categories; first, through using the volume calculation and second via statistical testing through the cloud to cloud comparison. Finding revealed that the mean differences for the test01 and test02 are about -20mm and 16mm, respectively. The Root Mean Square (RMS) and maximum error were found to be about ±63mm, 45cm and ±56 mm, 25cm for test01 and test02, respectively.